2020
DOI: 10.1111/ncn3.12391
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive brain stimulation and short‐term cortical plasticity

Abstract: Non‐invasive brain stimulation (NIBS) techniques have been widely used to study central nervous system pathophysiology and have revealed new information about the functional roles of specific brain structures. This review first outlines the basic technologies and neural mechanisms associated with NIBS. Transcranial magnetic stimulation (TMS) was first utilized to obtain motor‐evoked potentials, which reflect corticospinal tract function. Later, studies using repetitive TMS and patterned TMS‐like theta‐burst st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
1
0
2
Order By: Relevance
“…According to the above research results, the author adopts a multitarget-tracking task by changing the movement speed of the athletes in the expert group, the novice group, and the control group and explores the performance of visual attention tracking and neural oscillation characteristics in ice hockey players [10]. rough experiments, it was observed that the movement speed increased, whether it can reduce the individual's tracking performance and enhance the degree of neural oscillations, thereby reducing the inhibitory effect on nontarget tasks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the above research results, the author adopts a multitarget-tracking task by changing the movement speed of the athletes in the expert group, the novice group, and the control group and explores the performance of visual attention tracking and neural oscillation characteristics in ice hockey players [10]. rough experiments, it was observed that the movement speed increased, whether it can reduce the individual's tracking performance and enhance the degree of neural oscillations, thereby reducing the inhibitory effect on nontarget tasks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Людині без медичної освіти та досвіду буде важко користуватися приладом з неочевидною установкою параметрів, в яких вона не орієнтується. Отже існує потреба в розробці інтерфейса, який міг би підійти для використовування в стаціонарі та вдома [4].…”
Section: магнітна стимуляціяunclassified
“…Так, стимуляція лобової частки з частотою 20 Гц приводить до значного зростання рівня дофаміну в гіпокампі. Принцип терапевтичної магнітної стимуляції: виникає електромагнітне поле високої інтенсивності вільно проникає через кістки черепа і м'які тканини і впливає на глибокі нервові центри, периферичні нерви, головний і спинний мозок, недоступні для інших неінвазивних способів стимуляції [4].…”
Section: магнітна стимуляціяunclassified